Analisis Pola Persebaran Pencemaran Air Tanah di Sekitar Penambangan Sumur Minyak Tua Desa Wonocolo, Kedewan, Bojonegoro: Analysis of Groundwater Pollution Distribution Patterns Around the Mining of Old Oil Wells Wonocolo Village, Kedewan, Bojonegoro - Subariswanti; Hakim, Abdul; Suprayogi, Dedy (Departemen Teknik Sipil dan Lingkungan IPB, 2021)
Wonocolo Village is a traditional old oil well mining tourism area in Kedewan District, Bojonegoro Regency. This existence affects water quality because it is one of many factors causing groundwater pollution. The purpose study is to determine the distribution pattern of pollution such as iron, manganese, and zinc due to oil mining. Moreover, the study predicts the pattern of distribution of pollution in groundwater over a certain period of time. The method used for this study is groundwater modeling (MATLAB). Thus, determination of sampling based on SNI 6989.58:2008 with 3 (three) sampling points. The determination of the distribution pattern uses the parameters such as Iron, Manganese, and Zinc. The simulation results of the 2-dimensional distribution model and in the range in the next 18 years and 50 years. The prediction result for iron content is still in good condition. Meanwhile for manganese content and zinc content will be polluted after 50 years with a detected distance of ± 1150 m and ± 1400 m respectively from the contaminant source point.